2017
DOI: 10.1177/0141076817738499
|View full text |Cite
|
Sign up to set email alerts
|

Contract and ownership type of general practices and patient experience in England: multilevel analysis of a national cross-sectional survey

Abstract: Objective: To examine associations between the contract and ownership type of general practices and patient experience in England. Design: Multilevel linear regression analysis of a national cross-sectional patient survey (General Practice Patient Survey). Setting: All general practices in England in 2013–2014 (n ¼ 8017). Participants: 903,357 survey respondents aged 18 years or over and registered with a general practice for six months or more (34.3% of 2,631,209 questionnaires sent). Main outcome measures: P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…In the UK, general practices are privately owned businesses contracted to deliver primary care (Cowling et al, 2017). On the other hand, many general practices in New Zealand are private businesses, but are increasingly becoming a part of larger corporations or are owned by trusts in low‐socioeconomic areas (Goodyear‐Smith & Kassai, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, general practices are privately owned businesses contracted to deliver primary care (Cowling et al, 2017). On the other hand, many general practices in New Zealand are private businesses, but are increasingly becoming a part of larger corporations or are owned by trusts in low‐socioeconomic areas (Goodyear‐Smith & Kassai, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Co‐located services increased as well. In 2016, 81% of practices had pathology services on location versus 49% in 2010; for imaging, these figures are 30% versus 15% and for physiotherapy 50% versus 29% respectively 3,4 …”
mentioning
confidence: 99%
“…Corporatisation of general practice in New Zealand is rising as new generation GPs prefer a lower administrative burden 7 . While national policies in the United Kingdom have encouraged partnerships and the integration of general practices to improve service quality and facilitate access, most practice groups have remained independent businesses (< 5% corporate‐owned) 4 …”
mentioning
confidence: 99%
“…It appears that these concerns may have played out in practice: research published in 2017 showed that patients who were registered with general practices owned by limited companies reported worse experiences of care than other patients 34. There’s a legitimate concern that, if your eye is always on the bottom line, standards will shift towards the minimum you can get away with.…”
mentioning
confidence: 99%